2018
DOI: 10.1002/adfm.201801246
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Thermoelectric Polymer Composites Based on a Carbon Nanotubes Forest

Abstract: Polymer-based composites are of high interest in the field of thermoelectric (TE) materials because of their properties: abundance, low thermal conductivity, and nontoxicity. In applications, like TE for wearable energy harvesting, where low operating temperatures are required, polymer composites demonstrate compatible with the targeted specifications. The main challenge is reaching high TE efficiency. Fillers and chemical treatments can be used to enhance TE performance of the polymer matrix. The combined app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…In contrast to the parallel TE structure, the vertical TE device (which constitutes the conventional architecture for inorganic materials) sufficiently increases the temperature difference between the hot and cold sides through the thick TE layer . To construct a vertical TE generator using organic TE materials, Yusupov et al reported vertically aligned multiwalled carbon nanotube forests (VA‐CNTFs), which led to the realization of a high temperature gradient . The result demonstrates that an increase in the thickness of the active TE layer through vertical alignment induces an increase in the temperature difference for even a low input temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the parallel TE structure, the vertical TE device (which constitutes the conventional architecture for inorganic materials) sufficiently increases the temperature difference between the hot and cold sides through the thick TE layer . To construct a vertical TE generator using organic TE materials, Yusupov et al reported vertically aligned multiwalled carbon nanotube forests (VA‐CNTFs), which led to the realization of a high temperature gradient . The result demonstrates that an increase in the thickness of the active TE layer through vertical alignment induces an increase in the temperature difference for even a low input temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric conversion efficiency is usually evaluated by a dimensionless figure of merit ( ZT ), which is defined as ZT = S 2 σT/κ, where S is the Seebeck coefficient; σ and T stand for electrical conductivity and absolute temperature, respectively; and κ is the thermal conductivity. Otherwise, S 2 σ is called the power factor, which is usually used to evaluate the thermoelectric properties of organic polymer materials and their composites due to their low thermal conductivities …”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, S 2 σ is called the power factor, which is usually used to evaluate the thermoelectric properties of organic polymer materials and their composites due to their low thermal conductivities. [6][7][8][9][10] At present, the research of high-performance thermoelectric materials is still focused on inorganic thermoelectric materials, including Bi 2 Te 3 , Sb 2 Te 3 , PbTe, and some oxides. [11][12][13][14] Although inorganic thermoelectric materials have desirable thermoelectric properties, they also possess some inherent defects, for instance, high cost, toxicity, scarcity of elements, and processing difficulties.…”
Section: Doi: 101002/marc201900082mentioning
confidence: 99%
“… 27 One possible approach to overcome these drawbacks is directly using CNT arrays in which CNTs are already aligned. 28 Here, for the first time, we used a vertically aligned, highly ordered, CNT forest (CNTF) as a filler to improve the TE properties of P3HT. Additionally, the two additives, LiTFSI and tert -butylpyridine (TBP), were used to improve the electrical properties of the polymer film.…”
Section: Introductionmentioning
confidence: 99%